UNGKAPAN BERMAKNA BUDAYA DALAM SYAIR DANGISA MASYARAKAT BOLANGO DI BOLAANG MONGONDOW SELATAN - GOBEL, HYLDA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT All regions in Indonesia have a diversity of traditions that enrich the culture. It is also found in the sub-ethnic groups in the district Bolango Bolaang South Mongondow. One is a dangisa dance which is kind of a war dance. The poem of dangisa dance contains the cultural values ​​implicit in expressions. But the lack of public will culturally meaningful expressions in poetry led to cultural values ​​contained in it is no longer applied in social life. Therefore, the purpose of this study is to identify and explain those phrases and then find cultural meaning contained in the poem dangisa dance. The method used in this research is descriptive-qualitative method. To gather data, researchers conducted a study of the documents, and observations and interviews using interview techniques recommended Spradley (1997). The observations are then translated into engineering Etnography of Speaking by Hymes (1974). Identify and describe forms of lingual units, data were analyzed using linguistic theory proposed by Chaer (2007) and Djajasudarma (2009). Then, to find the meaning behind the cultural expressions that are used in poetry linguistic anthropological theory proposed by Foley (1997). The results showed that in poetry there dangisa dance-language expressions in the form of words, phrases, clauses, and sentences have meaning and significance in the form of broad, cognitive meaning, connotative meaning, idiomatic meaning, and emotive meaning. Cultural meaning in poetry is classified into 5 meaningful cultural expression. From the results of the research and the discussion concluded that the poem dance dangisa are speaking Bolango meaningful cultural expressions containing noble values. Keywords: Cultural Expression Poetry Community Dance Bolango